The versatile role of the ethynyl group in crystal packing: an interaction propensity study. Issue 3 (26th February 2016) - Allen, Frank H.; Wood, Peter A.; Galek, Peter T. A.
Abstract : It is well documented that the ethynyl group can act as a hydrogen‐bond donor via its acidic C—H, and as a hydrogen‐bond acceptor via the triple‐bond π‐density. Using the Cambridge Structural Database (CSD), it is shown that C—C[triple‐bond]C—H forms hydrogen bonds to N, O, S or halogens in 74% of structures in which these bonds can form. Additionally, the ethynyl group forms C—H...π interactions with itself or with phenyl groups in 23% of structures and accepts hydrogen bonds from O—H, N—H or C(aromatic)—H in 47% of structures where such bonds are possible. Overall, C—C[triple‐bond]C—H acts as a donor or acceptor in 87% of structures in which it occurs. These propensities for hydrogen‐bond formation have been determined using quite tight geometrical constraints, and many more ethynyl groups form interactions with only slight relaxations of these constraints. We conclude that the ethynyl group makes crucial contributions to molecular aggregation in crystal structures, and this is exemplified by hydrogen‐bond predictions for specific structures made using the statistical propensity tool now available in CSD system software.